Commuting Toeplitz Operators with Harmonic Symbols on $A^2 (\overline{\mathbb{D}}, dμ)$ (Communications in Mathematical Research, 2021)
For any given symmetric measure $µ$ on the closed unit disk $\overline{\mathbb{D}}$, we applythe Berezin transform to characterizing semi-commuting and commuting Toeplitzoperators with bounded harmonic symbols on $A^2 (\overline{\mathbb{D}}, dμ)$.